Matters of Spirit : J. G. Fichte and the Technological Imagination - Scribner, F. Scott (Book collections on Project MUSE., 2010)
"An interpretation of the philosophy of J.G. Fichte. Examines the impact of nineteenth-century psychological techniques and technologies on the formation of his theory of the imagination"--Provided by publisher.